Introduction of the ‘Blue Card’ Concussion Policy to Semi-Elite Australian Football: Medical Staff Experiences and Perceptions - Jacob R Msando; Gill Cowen; Sarah A Harris; Troy Kirkham; Myles C Murphy (International Journal of Sports Physical Therapy)
# Background